Preserving halal Integrity in herbs and herbal industry supply chain / Salini Rajendran and Nitty Hirawaty Kamarulzaman - Rajendran, Salini; Kamarulzaman, Nitty Hirawaty (Academy of Contemporary Islamic Studies (ACIS), 2017)
The rapid development of halal industry has significantly influences people’s tastes, habit, and spending patterns across the globe. Halal also influences an individual’s lifestyle as it offers a wide range of options which is not only limited to food items but also healthcare products, cosmetics, logistics and financial services. Consumers nowadays do not only demand for halal products, but are also aware of the halalan toyyibban concept which requires every activity in the production process to be halal, safe and not harmful. However, due to the complexities of supply chain activities, the halal status of a product might be at stake. This unfortunately has triggered consumers to raise questions on authenticity and integrity of the products. The scenario is worsen by the increasing number of fraudulent halal certifications as well as the physical contamination of halal products. Hence, it is a major challenge to preserve halal integrity among its players both in the local and international markets. Thus, the main objective of this paper is to provide an in-depth review on halal food supply chain management focusing on the herbal industry. The paper also highlights the issue of halal integrity in the industry.